New Insights Into Energy Substrate Utilization and Metabolic Remodeling in Cardiac Physiological Adaption - Shi, Xiaomeng; Qiu, Hongyu (Frontiers in Physiology, 2022)
Cardiac function highly relies on sufficient energy supply. Perturbations in myocardial energy metabolism play a causative role in cardiac pathogenesis. Accumulating evidence has suggested that modifications of cardiac metabolism are also an essential part of the adaptive responses to various physiological conditions in the heart to meet specific energy needs. The review highlighted some new studies on basic myocardial energy substrate metabolism and updated recent findings regarding cardiac metabolic remodeling and their associated mechanisms under physiological conditions, including exercise and cardiac development. Studying basic metabolic profiles in the heart in these conditions can contribute to understanding the significance of metabolic regulation in the heart during physiological adaption and gaining further insights into the maladaptive metabolic changes associated with cardiac pathogenesis, thus opening up new avenues to exploring novel therapeutic strategies in cardiac diseases.